Legal Analysis of Land Certification Policy from the Perspective of Legal Certainty of Land Rights - Safitri, Widia; Isnaeni, Diyan; Misranto, Misranto (Journal La Sociale, 2025)
This study aims to analyze land certification policies in order to realize legal certainty of land rights, with a focus on the implementation of the Complete Systematic Land Registration (PTSL) program in Raas District, Sumenep Regency. The method used in this study is a normative juridical method with a legislative and conceptual approach. Data sources were obtained from primary legal materials such as the Basic Agrarian Law, Government Regulation No. 24 of 1997, and Regulation of the Minister of ATR/BPN No. 6 of 2018, supported by secondary legal materials in the form of scientific journals, books, and reports from related agencies. The results of the study indicate that the PTSL program has been normatively designed to provide legal protection for community land rights, however, its implementation in Raas District is still faced with various obstacles. These include low community participation, limited ownership documents, land boundary issues, and a lack of community legal understanding. Although the policy is aligned with the principle of legal certainty, its effectiveness is hampered by the lack of resources, infrastructure, and accessibility in the island region. This indicates a gap between legal norms and social reality. This study recommends the need to strengthen inter-institutional coordination, increase land service capacity, and provide ongoing legal outreach to ensure equitable and just legal certainty for communities in remote areas.